MicroRNA-30 family members regulate calcium/calcineurin signaling in podocytes - Wu, Junnan; Zheng, Chunxia; Wang, Xiao; Yun, Shifeng; Zhao, Yue; Liu, Lin; Lu, Yuqiu; Ye, Yuting; Zhu, Xiaodong; Zhang, Changming; Shi, Shaolin; Liu, Zhihong (The Journal of Clinical Investigation, 2015)
Calcium/calcineurin signaling is critical for normal cellular physiology. Abnormalities in this pathway cause many diseases, including podocytopathy; therefore, understanding the mechanisms that underlie the regulation of calcium/calcineurin signaling is essential. Here, we showed that critical components of calcium/calcineurin signaling, including TRPC6, PPP3CA, PPP3CB, PPP3R1, and NFATC3, are the targets of the microRNA-30 family (miR-30s). We found that these 5 genes are highly expressed as mRNA, but the level of the proteins is low in normal podocytes. Conversely, protein levels were markedly elevated in podocytes from rats treated with puromycin aminonucleoside (PAN) and from patients with focal segmental glomerulosclerosis (FSGS). In both FSGS patients and PAN-treated rats, miR-30s were downregulated in podocytes. In cultured podocytes, PAN or a miR-30 sponge increased TRPC6, PPP3CA, PPP3CB, PPP3R1, and NFATC3 expression; calcium influx; intracellular Ca2+ concentration; and calcineurin activity. Moreover, NFATC3 nuclear translocation, synaptopodin degradation, integrin β3 (ITGB3) activation, and actin fiber loss, which are downstream of calcium/calcineurin signaling, were induced by miR-30 reduction but blocked by the calcineurin inhibitor FK506. Podocyte-specific expression of the miR-30 sponge in mice increased calcium/calcineurin pathway component protein expression and calcineurin activity. The mice developed podocyte foot process effacement and proteinuria, which were prevented by FK506. miR-30s also regulated calcium/calcineurin signaling in cardiomyocytes. Together, our results identify miR-30s as essential regulators of calcium/calcineurin signaling.